HADITS DITINJUAN DARI KUALITASNYA - Delisa Delisa; Ahmad Zabidi (ADISAM PUBLISHER, 2024)
Hadith is every word, action, or decree attributed to the Prophet Muhammad SAW. In other languages, hadith is any information attributed to the Prophet Muhammad SAW. For example, when we say